PROPOSALS FOR IMPROVING FUNDS STATEMENTS. - Corbin, Donald A. (The Accounting Review, 1961)
It is generally agreed that the purpose of any financial statement is to present useful information for decision-making by its readers. The growing popularity of the sources and applications of funds statement (hereafter referred to as the funds statement) indicates that this report presents information which is not readily found in the typical income statement or balance sheet. In meeting this need, accountants should determine what information is desired by readers of funds statements and then should design an appropriate report. A contemporary accounting scholar, Louis Goldberg. strongly dissented from this acceptance in 1951, stating that the shift in emphasis has been in the wrong direction and that the earlier concepts were more cogent, more satisfying and more rational. A shift out of cash into inventories, voluntary, or vice versa, might he one of the most significant financial changes during a period. Similarly a large decline in notes payable and increase in open accounts, or vice versa, may foretell an important change in financial or credit policy. These and analogous types of changes within working capital are not revealed in the orthodox statement.